2008
DOI: 10.1002/hep.22441
|View full text |Cite
|
Sign up to set email alerts
|

Utility of serum tumor markers, imaging, and biliary cytology for detecting cholangiocarcinoma in primary sclerosing cholangitis†

Abstract: There is limited information on test performance for detecting cholangiocarcinoma in primary sclerosing cholangitis (PSC), particularly when used sequentially. This study aimed to characterize diagnostic performance of serum carbohydrate antigen 19-9 (CA 19-9), ultrasonography, computed tomography, magnetic resonance imaging, cholangiography, and biliary cytologic techniques for detecting cholangiocarcinoma in PSC. All consecutive patients with PSC were screened and followed for development of cholangiocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
345
0
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(358 citation statements)
references
References 34 publications
3
345
0
10
Order By: Relevance
“…Multimodal approaches, including a combination of laboratory tests, cross‐sectional imaging, and endoscopic testing, are frequently required for this purpose. Use of serum CA 19‐9 in combination with ultrasonography, computed tomography, or magnetic resonance imaging has been reported to have a sensitivity of 91%, 100%, and 96%, respectively (when at least one modality is positive) 35. Conversely, individual tests generally have suboptimal performance characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multimodal approaches, including a combination of laboratory tests, cross‐sectional imaging, and endoscopic testing, are frequently required for this purpose. Use of serum CA 19‐9 in combination with ultrasonography, computed tomography, or magnetic resonance imaging has been reported to have a sensitivity of 91%, 100%, and 96%, respectively (when at least one modality is positive) 35. Conversely, individual tests generally have suboptimal performance characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, individual tests generally have suboptimal performance characteristics. For example, conventional brush cytology has excellent specificity (nearly 100%) but limited sensitivity (ranging from 18%‐40%) in diagnosing CCA 15, 35, 36, 37, 38, 39. Similarly, while serum CA 19‐9 has a reported sensitivity and specificity of 79% and 98%, respectively, at a cut‐off value of 130 U/mL,40 its levels may become elevated in the setting of nonmalignant obstruction or acute cholangitis, and it is undetectable in Lewis blood antigen‐negative patients (and remains so even in the presence of CCA) 41.…”
Section: Discussionmentioning
confidence: 99%
“…5 ERCP with brush cytology and tumor markers has been applied to PSC patients for the detection of CC with limited success. 6 Therefore, the entire biliary epithelium is at risk of a malignant transformation. Bergquist et al 7 showed that more than 60% of patients with PSC have bile duct dysplasia in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…In regard to CC, screening strategies employing imaging techniques, preferentially with MRI, but also ultrasound and computed tomography, in association with tumor biomarkers have been suggested strategies (241,244) , but their accuracy in detecting CC was reported to be low (244,245) . The most commonly employing biomarker for CC in PSC is CA19-9.…”
Section: Screening and Management Of Cholangiocarcinomamentioning
confidence: 99%